Respuesta :

Answer:

Step-by-step explanation:

11)[tex]4b^{\frac{-3}{4}}+10=\frac{21}{2}\\\\4b^{\frac{-3}{4}}=\frac{21}{2}-10\\\\4b^{\frac{-3}{4}}=\frac{21}{2}-\frac{10*2}{1*2}\\\\4b^{\frac{-3}{4}}=\frac{21}{2}-\frac{20}{2}\\\\4b^{\frac{-3}{4}}=\frac{21-20}{2}\\\\4b^{\frac{-3}{4}}=\frac{1}{2}\\\\b^{\frac{-3}{4}}=\frac{1}{2*4}\\\\\frac{1}{b^{\frac{3}{4}}}=\frac{1}{8}\\\\1*8=b^{\frac{3}{4}}\\\\2^{3}=( b^{\frac{1}{4}})^{3}\\\\2= b^{\frac{1}{4}}\\\\Take power 4 both sides,\\2^{4}=b\\b=16[/tex]

Ver imagen devishri1977
ACCESS MORE